Phylogenetic analysis of endogenous viral elements in the rice genome reveals local chromosomal evolution in Oryza AA-genome species - Saito, Nozomi; Chen, Sunlu; Kitajima, Katsuya; Zhou, Zhitong; Koide, Yohei; Encabo, Jaymee R.; Diaz, Maria Genaleen Q.; Choi, Il-Ryong; Koyanagi, Kanako O.; Kishima, Yuji (Frontiers in Plant Science, 2023)
Rice genomes contain endogenous viral elements homologous to rice tungro bacilliform virus (RTBV) from the pararetrovirus family Caulimoviridae. These viral elements, known as endogenous RTBV-like sequences (eRTBVLs), comprise five subfamilies, eRTBVL-A, -B, -C, -D, and -X. Four subfamilies (A, B, C, and X) are present to a limited degree in the genomes of the Asian cultivated rice Oryza sativa (spp. japonica and indica) and the closely related wild species Oryza rufipogon. The eRTBVL-D sequences are widely distributed within these and other Oryza AA-genome species. Fifteen eRTBVL-D segments identified in the japonica (Nipponbare) genome occur mostly at orthologous chromosomal positions in other AA-genome species. The eRTBVL-D sequences were inserted into the genomes just before speciation of the AAgenome species. Ten eRTBVL-D segments are located at six loci, which were used for our evolutionary analyses during the speciation of the AA-genome species. The degree of genetic differentiation varied among the eRTBVL-D segments. Of the six loci, three showed phylogenetic trees consistent with the standard speciation pattern (SSP) of the AA-genome species (Type A), and the other three represented phylogenies different from the SSP (Type B). The atypical phylogenetic trees for the Type B loci revealed chromosome region-specific evolution among the AA-genome species that is associated with phylogenetic incongruences: complex genome rearrangements between eRTBVL-D segments, an introgression between the distant species, and low genetic diversity of a 3 shared eRTBVL-D segment. Using eRTBVL-D as an indicator, this study revealed the phylogenetic incongruence of local chromosomal regions with different topologies that developed during speciation.